Opening ideological and implementational spaces for multilingual/plurilingual policies and practices in education: a snapshot of scholarly activism in Pakistan. Issue 5 (20th October 2019) - Manan, Syed Abdul; David, Maya Khemlani; Channa, Liaquat Ali
ABSTRACT: The study proposes that Critical Multilingual Language Awareness (CMLA) can be deployed as a productive theoretical construct for scholarly activism in a country such as Pakistan where multilingualism and linguistic diversity have historically been seen as problems than assets in education. We illustrate that such activism can transform orientations and deconstruct myths/misconceptions about bi/multilingual/plurilingual education as research suggests greater public glorification of the dominant languages such as English and Urdu vis-à-vis native languages. Given the subtractive linguistic ecology, this paper explores how prevailing orientations about native languages can be neutralized and positively transformed. The study suggests how scholars/researchers or activists can create 'ideological and implementational spaces' [Hornberger, N. H. (2003). Continua of biliteracy: An ecological framework for educational policy, research, and practice in multilingual settings . Clevedon: Multilingual Matters; Hornberger, N. H. (2016). Researching the continua of biliteracy. In K. King, Y.-J. Lai, & S. May (Eds.), Research methods in language and education (pp. 1–18). Cham: Springer International] for multiple languages, literacies, and identities in classroom, community, and society. The participants were students of Bilingualism course enrolled for MPhil program in a public sector university in Pakistan. Data were analyzed through the constructs of critical applied linguistics and Critical Multilingual Language Awareness (CMLA) [García, O. (2017). Critical multilingual language awareness and teacher education. In J. Cenoz, D. Gorter, & S. May (Eds.), Language awareness and multilingualism (pp. 263–280). Cham: Springer International Publishing]. The study shows that lack of critical awareness and education primarily causes disinterest in bi/multilingual/plurilingual. Findings suggest that exposure to critical scholarship, and sensitization about the value of bi/multilingual/plurilingual education and linguistic/cultural diversity can create spaces, and impact significant theoretical, ideological/political and implementational transformations.